FINANCING OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article examines the economics of financing small business in private equity and debt markets. Firms are viewed through a financial growth cycle paradigm in which different capital structures are optimal at different points in the cycle. This study and study of the specifics of the financial and credit mechanism in foreign countries is an important factor in determining the optimal directions of financial and credit support for small businesses and private entrepreneurship in the Republic of Uzbekistan. The purpose of the study of the financial and credit mechanism for supporting small business in foreign countries is to formulate the main directions for improving small support based onthe analytical data.